Physico-chemical characteristics and sensory profile of kesong puti coated with guar gum - Maramba, Natalie C.; Francisco, Ma. Leonora dL. (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
Kesong puti or soft white cheese is a local dairy product of the Philippines made from pasteurized carabao or goat milk. Because of its high moisture content and current packaging, it has a shelf life of approximately four to five days at room temperature and up to seven days if refrigerated. Guar gum, a widely-used galactomannan-based edible coating also utilized in dairy products such as cheese, was applied to kesong puti in this study. The effect of varying concentration of guar gum solution (1%, 1.5% and 2%) on the kesong puti samples was done during storage at a refrigerated temperature (3-5oC) for seven days. Samples with no coating were used as control. pH of kesong puti increased when coated with guar gum. Color, % titrable acidity and firmness of kesong puti were unaffected by guar gum coating. Results showed no significant improvement in the physico-chemical and sensorial properties (except for gloss) of the kesong puti samples.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Cheese -- Philippines; Cheese tasting -- Philippines